The Ontology of Vision. The Invisible, Consciousness of Living Matter - Fiorio, Giorgia (Frontiers in Psychology, 2016)
If I close my eyes, the absence of light activates the peripheral cells devoted to the perception of darkness. The awareness of ‘seeing oneself seeing’ is in its essence a thought, one that is internal to the vision and previous to any object of sight. To this amphibious faculty, the “diaphanous color of darkness”, Aristotle assigns the principle of knowledge. “Vision is a whole perceptual system, not a channel of sense”. Functions of vision are interweaved to the texture of human interaction within a terrestrial environment that is in turn contained into the cosmic order. Within the internal resonance of a double reflection, the living being is the transitive host between two orders of scale, both bigger and smaller than the individual and unity. In the perceptual integrative system of human vision, the convergence-divergence of the corporeal presence and the diffraction of its own appearance is the margin. The sensation of being no longer coincides with the breath of life, it does not seems ‘real’ without the trace of some visible evidence and its simultaneous ‘sharing.’ Without a shadow, without an imprint, and destined for multiple invisible witnesses, the numeric copia of the physical presence inhabits the transient memory of our electronic prostheses. A rudimentary ‘visuality’ replaces tangible experience dissipating its meaning and the awareness of being alive. Transversal to the civilizations of the ancient world, through different orders of function and status, the anthropomorphic figuration of archaic sculpture questions the “idea of Being.” Ancient statues do not appear in order to be visible as artworks, but rather to exist. The awareness of human finiteness seals the compulsion to ‘give body’ to an invisible apparition that shapes the figuration of Being as the corporeal expression of an ontogenetic waking of human consciousness. Subject and object, the term “humanum” fathoms the relationship between matter and its living dimension, “this de facto vision and the ‘there is’ which it contains.” The project reconsiders the rift between the terms vision–presence in the contemporary perception of anthropomorphic figuration according to the immaterial heritage of archaic human statuary and the esoteric legacy of its origins.